A link between inflammation and thrombosis in atherosclerotic cardiovascular diseases: Clinical and therapeutic implications. (September 2020) - Oikonomou, Evangelos; Leopoulou, Marianna; Theofilis, Panagiotis; Antonopoulos, Alexios S.; Siasos, Gerasimos; Latsios, George; Mystakidi, Vasiliki Chara; Antoniades, Charalambos; Tousoulis, Dimitris
Abstract: The association between thrombosis and acute coronary syndromes is well established. Inflammation and activation of innate and adaptive immunity are another important factor implicated in atherosclerosis. However, the exact interactions between thrombosis and inflammation in atherosclerosis are less well understood. Accumulating data suggest a firm interaction between these two key pathophysiologic processes. Pro-inflammatory cytokines, such as tumor necrosis factor α, interleukin-6 and interleukin-1, have been implicated in the thrombotic cascade following plaque rupture and myocardial infarction. Furthermore, cell adhesion molecules accelerate not only atheromatosis but also thrombosis formation while activated platelets are able to trigger leukocyte adhesion and accumulation. Additionally, tissue factor, thrombin, and activated coagulation factors induce the release of pro-inflammatory cytokines such as prostaglandin and C reactive protein, which may further induce von Willebrand factor secretion. Treatments targeting immune activation (i.e. interleukin-1 inhibitors, colchicine, statins, etc.) may also beneficially modulate platelet activation while common anti-thrombotic therapies appear to attenuate the inflammatory process. Taken together in the context of cardiovascular diseases, thrombosis and inflammation should be studied and managed as a common entity under the concept of thrombo-inflammation. Graphical abstract: Image 1 Highlights: Thrombosis and inflammation are both involved in atherosclerosis progression. Interaction between these two processes supports the concept of thromboinflammation. Low grade inflammation promotes coagulation and platelet activation and vice versa . In contrast to platelet inhibition, anti-inflammatory approaches are not applied in clinical practice. Targeting both thrombosis and inflammation may address residual cardiovascular risk.